Positive electrode active material and positive electrode comprising same

By adjusting the D50, nodule particle size and coating layer cobalt content of the high nickel positive electrode active material, ensuring that the X/Y/Z ratio is within a specific range, the problem of positive electrode deterioration and cracking of lithium secondary batteries during circulation is solved, and the problem of positive electrode deterioration and cracking of lithium secondary batteries is achieved. Improved battery life and output performance.

CN119234328APending Publication Date: 2024-12-31LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041739.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-15
Filing Date
2023-12-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing lithium secondary batteries have deteriorated and cracked positive electrodes due to volume expansion-contraction during circulation, reducing battery capacity and increasing resistance, especially when using high-nickel positive electrode active materials, which leads to a short life.

Method used

By adjusting the average particle size of D50, nodules and the content of cobalt in the surface coating layer in single-particle or quasi-single-particle high-nickel positive electrode active material, ensure that the X/Y/Z ratio is within the range of 1≤XY/Z≤3 Inside, a stable coating is formed to reduce surface resistance and reduce cracking.

Benefits of technology

The cycle life characteristics of lithium secondary batteries are improved, the resistance is reduced, and the output performance is excellent, and the energy density and thermal stability are maintained under high temperature conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material comprising: a nickel-based lithium composite metal oxide in the form of a single particle or a quasi-single particle, the nickel-based lithium composite metal oxide having a Ni content of 80 at% or more in a transition metal other than lithium; and a coating layer on a surface of the nickel-based lithium composite metal oxide and containing cobalt, in which the positive electrode active material satisfies Formula 1 below. [Formula 1] 1 < = XY / Z < = 3. In the above formula 1, X (mol%) is the number of moles of Co in the coating layer based on 100 moles of the nickel-based lithium composite metal oxide, Y ([mu] m) is the average particle diameter of the nodule of the nickel-based lithium composite metal oxide, Z ([mu] m) is D50 of the positive electrode active material, and Z is 5 [mu] m to 12 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0176301 filed in the Korean Intellectual Property Office on December 15, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a positive electrode active material and a positive electrode comprising the same. Background Art

[0004] With the development of science and technology and the increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density, high voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, with the recent development of technologies such as electric vehicles, the demand for high-capacity secondary batteries is increasing.

[0005] When a lithium secondary battery is driven, volume expansion-contraction occurs repeatedly during the cycle, so the positive electrode deteriorates and cracks, which reduces the capacity of the battery cell and increases the resistance. In particular, when a high-nickel positive electrode active material with a Ni content of 80 atomic % or more is used to increase the capacity of the secondary battery, the structural stability is reduced, resulting in a large number of cracks, so that the life of the secondary battery is seriously deteriorated as the cycle progresses.

[0006] In order to overcome these shortcomings, single particles or quasi-single particles can be used. However, when using a single particle or quasi-single particle form of a positive electrode active material, the contact interface with the electrolyte is reduced, so there are the following problems: the lithium ion diffusion path is longer than that of a conventional secondary particle form of a positive electrode active material, and the output performance is poor due to the formation of a surface rock salt structure due to over-firing. Such output performance degradation tends to increase with the increase in the size of the single particle or quasi-single particle.

[0007] Therefore, in order to compensate for the problem of single particles, lithium secondary batteries are usually manufactured by mixing small diameter particles and secondary particles in a bimodal manner. However, when a bimodal positive electrode active material is applied as described above, there is a problem that the relatively fragile secondary particles are further broken and thus the side reactions with the electrolyte are increased. Summary of the invention

[0008] [Technical issues]

[0009] One aspect of the present invention is to provide a high nickel cathode active material in the form of a single particle or quasi-single particle having excellent lifespan properties and excellent overall properties (such as capacity and output properties) and a secondary battery using the cathode active material.

[0010] [Technical solution]

[0011] Through extensive and intensive research and experiments to solve the above problems, the inventors of the present invention have found that the above purpose can be achieved by adding D of the positive electrode active material to a single particle or quasi-single particle high nickel positive electrode active material. 50 This is achieved by adjusting the average particle size of the nodules and the content of Co contained in the coating layer formed on the surface of the positive electrode active material to an appropriate ratio.

[0012] Specifically, according to one aspect of the present invention, a positive electrode active material is provided, which comprises a nickel-based lithium composite metal oxide and a coating layer, wherein the nickel-based lithium composite metal oxide has a Ni content of more than 80 atomic % in transition metals other than lithium and is in the form of a single particle or a quasi-single particle, and the coating layer is located on the surface of the nickel-based lithium composite metal oxide and contains cobalt, wherein the positive electrode active material satisfies the following Formula 1.

[0013] [Formula 1] 1≤XY / Z≤3

[0014] In the above formula 1, X (mol%) is the molar number of Co in the coating layer based on 100 moles of the nickel-based lithium composite metal oxide, Y (μm) is the average particle size of the nodules of the nickel-based lithium composite metal oxide, and Z (μm) is the D of the positive electrode active material. 50 , and Z is 5 μm to 12 μm.

[0015] According to another aspect of the present invention, there is provided a positive electrode including a positive electrode active material layer, wherein the positive electrode active material layer contains the positive electrode active material.

[0016] [Beneficial Effects]

[0017] In the single particle or quasi-single particle form of high nickel positive electrode active material, the present invention can be achieved by adding D 50 , the average particle size of nodules and the content of Co contained in the coating layer formed on the surface of the positive electrode active material are adjusted to an appropriate ratio to achieve the effects of reducing the surface resistance and reducing the occurrence of cracks.

[0018] That is, the inventors of the present invention have found that the interface resistance of the positive electrode active material can be minimized by controlling the number of nodules and the cobalt coating amount of each of the positive electrode active material particles within a range satisfying a specific formula.

[0019] That is, a lithium secondary battery including a positive electrode to which the positive electrode active material of the present invention is applied has the effects of improving life properties during cycles, low resistance, and excellent output properties. DETAILED DESCRIPTION

[0020] Hereinafter, the present invention will be described in more detail.

[0021] It will be understood that the terms or words used in the present specification and claims should not be interpreted as having the meanings defined in commonly used dictionaries, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to best interpret the present invention.

[0022] In the present invention, a "single particle" is a particle composed of a single nodule. In the present invention, a "quasi-single particle" refers to a particle that is a composite composed of 10 or less nodules.

[0023] In the present invention, "nodules" refer to particle units constituting single particles and quasi-single particles, wherein the nodules may be single crystals without grain boundaries, or may be polycrystalline that appear to have no grain boundaries when observed using a scanning electron microscope (SEM) within a field of view of 5,000 to 20,000 times.

[0024] In the present invention, "secondary particles" refer to particles formed by agglomeration of tens to hundreds of primary particles. More specifically, secondary particles are agglomerates of 40 or more primary particles.

[0025] The term "particle" used in the present invention may include any one or all of a single particle, a quasi-single particle, a primary particle, a nodule, and a secondary particle.

[0026] In the present invention, "Dn" of the positive electrode active material refers to the particle size at the n% point in the volume cumulative distribution according to the particle size. That is, D 50 is the particle size at the 50% point in the volume cumulative distribution of particle sizes, and D 90 is the particle size at the 90% point in the volume cumulative distribution of particle sizes, and D 10 Dn is the particle size at the 10% point in the volume cumulative distribution according to the particle size. Dn can be measured using a laser diffraction method. Specifically, the powder to be tested is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (such as Microtrac S3500) to measure the difference in diffraction pattern with particle size when the particles pass through the laser beam, thereby calculating the particle size distribution. D 10 , D 50 and D 90 It can be measured by calculating the particle diameters at 10%, 50%, and 90% points in the volume cumulative distribution according to the particle diameters in a measuring device, respectively.

[0027] In the present invention, "nodule" means the smallest particle unit that is distinguished as a block when observing the cross section of the positive electrode active material by a scanning electron microscope (SEM), and may be formed by one crystal grain or by a plurality of crystal grains. The average particle size of the nodule can be measured by measuring the size of each particle distinguished in the cross-sectional SEM image of the positive electrode active material particle and obtaining the arithmetic mean thereof.

[0028] In the present invention, the "average grain size" is measured by analyzing the XRD data obtained by X-ray diffraction analysis of the positive electrode active material powder using the Rietveld refinement method. At this time, a Bruker D8 Endeavor (light source: Cu-Kα, ), the sample is placed in the groove of a conventional powder holder, and then the sample surface is evenly leveled with a glass slide, and the groove is filled with the sample so that the height of the sample is the same as the height of the edge of the holder, and X-ray diffraction analysis is performed under the conditions of FDS 0.5° and 2θ=15° to 90° region, step length=0.02° and total scanning time=about 20 minutes. Considering the charge in each site (metal in the transition metal site is +3, Ni in the Li site is +2) and cation mixing, the measurement data is Rietveld refined. Specifically, for instrumental broadening during particle size analysis, the fundamental parameter method (FPA) implemented in the Bruker TOPAS program is used, and all peaks in the measurement range are used in fitting. Among the peak shapes available in TOPAS, only the Lorentz contribution is used as the first principle (FP) to fit the peak shape, and strain is not considered.

[0029] In the present invention, "strain" refers to lattice distortion caused by defects, i.e., micro deformation. The XRD data obtained by X-ray diffraction analysis of the positive electrode active material powder was analyzed by Rietveld refinement method to measure strain. At this time, a Bruker D8 Endeavor (light source: Cu-Kα, ), the sample is placed in the groove of a conventional powder holder, and then the sample surface is evenly leveled using a slide glass, and the groove is filled with the sample so that the height of the sample is the same as the height of the edge of the holder. For FDS 0.5° and 2θ=15° to 90° region, X-ray diffraction analysis is performed under the conditions of step length=0.02° and total scanning time=about 20 minutes. Considering the charge in each site (metal in the transition metal site is +3, Ni in the Li site is +2) and cation mixing, the measurement data is Rietveld refined. Specifically, for instrument broadening during strain analysis, the fundamental parameter method (FPA) implemented in the Bruker TOPAS program is used, and all peaks in the measurement range are used in fitting. Among the peak shapes available in TOPAS, only the Lorentz contribution is used as the first principle (FP) to fit the peak shape.

[0030] Positive electrode active material

[0031] The positive electrode active material of the present invention is characterized by satisfying Formula 1 below.

[0032] [Formula 1] 1≤XY / Z≤3

[0033] Generally, since cobalt promotes the formation of a layered structure, it is known that when the cobalt content is high, the resistance of the positive electrode active material decreases. In addition, when the positive electrode active material is composed of a large number of agglomerates of primary particles, the interface between the primary particles and the primary particles becomes a migration path for lithium ions, and therefore, it is known that the more interfaces between the primary particles, the higher the lithium mobility, which reduces the resistance. However, according to the research of the inventors of the present invention, in the case of high-nickel positive electrode active materials in the form of single particles or quasi-single particles, it has been determined that if the cobalt content and the number of interfaces between nodules in the active material particles satisfy a specific relationship, there is an effect of suppressing resistance. At this time, the number of interfaces between nodules in the particles can be defined as D of the positive electrode active material. 50 The ratio of the average particle size (Z) to the average particle size (Y) of the nodules. Specifically, in the case of a high nickel positive electrode active material in the form of a single particle or a quasi-single particle, it has been determined that even if the Co content is high, if the Z / Y value does not meet a specific range, the resistance increases, and even if the Z / Y value increases, if the Co content does not meet a specific range, the resistance increases.

[0034] In the above formula 1, X (mol%) is the molar number of Co in the coating layer relative to 100 moles of the nickel-based lithium composite metal oxide. X may be 1 to 5 mol%, preferably, 1 to 3 mol%. When the cobalt content in the coating layer satisfies the above range, the microstructure of the single-particle and / or quasi-single-particle nickel-based lithium composite metal oxide is stabilized, thereby reducing the occurrence of cracking, and thus the collapse of the positive electrode active material can be suppressed even when cycling.

[0035] In the above formula 1, Y (μm) is the average particle size of the nodules of the nickel-based lithium composite metal oxide. Y can be 1 μm to 10 μm, preferably 6 μm to 8 μm, and most preferably 2 μm to 7 μm. When the average particle size (μm) of the nodules of the nickel-based lithium composite metal oxide meets the above range, the specific surface area is reduced, so the high temperature durability is excellent, the particle breakage is reduced, and therefore the gas is reduced when the lithium secondary battery is running.

[0036] In the above formula 1, Z (μm) is the D 50 Z may be 5 μm to 12 μm, preferably 6 μm to 10 μm, and most preferably 6.2 μm to 8 μm. 50 The cathode active material of the present invention has a D of 1.340 μm and a D of 1.340 μm. The cathode active material of the present invention has a D of 1.340 μm and a D of 1.340 μm. 50 Within the above range, there is no problem of slurry agglomeration, and excellent electrolyte impregnation property is achieved, thus having the effect that the output and life properties of a lithium secondary battery including the cathode active material are excellent.

[0037] In the above Formula 1, Z / Y refers to the number of nodules contained in a single positive electrode active material particle or the number of interfaces between nodules in an active material particle.

[0038] In the positive electrode active material of the present invention, Z / Y may be 1 to 3, preferably 1 to 2, and most preferably 1.1 to 1.5. 50 When the above range is met, the particle strength is high and the calendering density is high, which is suitable for forming a high energy density electrode. Even when the calendering rate is high, the particle breakage is still less, thereby improving the life properties and high temperature storage properties.

[0039] In the cathode active material of the present invention, a ratio of the cathode active material having a size of 5 μm to 7 μm may be 80 volume % or more relative to the entire cathode active material.

[0040] The content of lithium byproducts in the positive electrode active material of the present invention may be 1 mol % to 5 mol %, preferably 1 mol % to 3 mol % relative to the nickel-based lithium composite metal oxide. The positive electrode active material of the present invention is characterized in that it has a small amount of lithium byproducts even when over-fired to include a single particle.

[0041] The positive electrode active material of the present invention comprises a nickel-based lithium composite metal oxide and a coating layer. The nickel-based lithium composite metal oxide has a Ni content of 80 atomic% or more among transition metals other than lithium and is in the form of single particles or quasi-single particles. The coating layer is located on the surface of the nickel-based lithium composite metal oxide and contains cobalt.

[0042] The nickel content of the nickel-based lithium composite metal oxide contained in the positive electrode active material of the present invention can be 80 atomic% or more, preferably 85 atomic% or more. When the nickel is less than 80 atomic%, the capacity of the positive electrode active material decreases, and thus there is a problem that the positive electrode active material cannot be applied to an electrochemical device that requires a high capacity.

[0043] Specifically, the nickel-based lithium composite metal oxide contained in the positive electrode active material of the present invention may have a composition represented by the following formula 2.

[0044] [Formula 2]

[0045] Li a Ni b Co c M 1 d M 2 e O2

[0046] In the above formula 2, M 1 may be Mn, Al, or a combination thereof, and M 2 may be one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb.

[0047] a represents the molar ratio of lithium in the nickel-based lithium composite metal oxide and may satisfy 0.80 ≤ a ≤ 1.2, preferably 0.95 ≤ a ≤ 1.08, and more preferably 1 ≤ a ≤ 1.08.

[0048] b represents the molar ratio of nickel among metal elements other than lithium in the nickel-based lithium composite metal oxide and may satisfy 0.80 ≤ b ≤ 0.95 or 0.83 ≤ b ≤ 0.93. When the nickel content satisfies the above range, high-capacity properties can be achieved.

[0049] c represents the molar ratio of cobalt among metal elements other than lithium in the nickel-based lithium composite metal oxide and may satisfy 0 < c < 0.20, 0 < c ≤ 0.15, or 0.01 ≤ c ≤ 0.10.

[0050] d represents the molar ratio of M 1 among metal elements other than lithium in the nickel-based lithium composite metal oxide and may satisfy 0 < d < 0.20, 0 < d ≤ 0.15, or 0.01 ≤ d ≤ 0.10.

[0051] e represents the metal element M other than lithium in the nickel-based lithium composite metal oxide. 2 The molar ratio may satisfy 0≤e≤0.10, or 0≤e≤0.05.

[0052] Generally, spherical secondary particles formed by agglomeration of tens to hundreds of primary particles are generally used as positive electrode active materials for lithium secondary batteries. However, in the case of positive electrode active materials in the form of secondary particles formed by agglomeration of a large number of primary particles, particle crushing of primary particles falling off is prone to occur during the rolling process when manufacturing the positive electrode, and there is a problem of cracking inside the particles during the charge and discharge process. When the particles of the positive electrode active material are crushed or cracking occurs inside the particles, the contact area with the electrolyte increases, so there is a problem of increased gas production due to side reactions with the electrolyte.

[0053] In contrast, the particle strength of the positive electrode active material in the form of a single particle composed of one primary particle or a quasi-single particle formed by agglomeration of less than 10 primary particles is higher than that of the conventional positive electrode active material in the form of a secondary particle formed by agglomeration of tens to hundreds of primary particles, so that almost no particle crushing occurs during the rolling process. In addition, in the case of a single particle or quasi-single particle positive electrode active material, the number of primary particles constituting the particle is small, and the change caused by the volume expansion and contraction of the primary particles during the charge and discharge process is small, so the occurrence of cracking inside the particle is significantly reduced.

[0054] Therefore, when a positive electrode active material composed of a single particle and / or a quasi-single particle is used, a decrease in lifespan properties caused by the occurrence of particle crushing and internal cracking can be significantly suppressed.

[0055] The average crystal size of the nickel-based lithium composite metal oxide may be 170 nm to 300 nm, preferably 170 nm to 250 nm, and most preferably 180 nm to 230 nm. When the average crystal size is satisfied, an appropriate degree of sintering is achieved, and therefore, since the surface rock salt structure is rarely formed, the output performance is excellent.

[0056] The strain value of nickel-based lithium composite metal oxides can be 200×10 -6 Up to 380×10 -6 , preferably 210×10 -6 Up to 370×10 -6 When the above strain range is satisfied, the degree of completion of the crystal structure is high, and thus the positive electrode active material has a stable crystal structure and has excellent life performance.

[0057] The positive electrode active material of the present invention includes a coating layer on the surface of the nickel-based lithium composite metal oxide. The coating layer is formed on the surface of the positive electrode active material and on the surface of part or all of the nodules, and may include cobalt.

[0058] Specifically, the coating layer may have a composition represented by Formula 3 below.

[0059] [Formula 3]

[0060] Li x Co y O2

[0061] x represents a molar ratio of lithium in the coating layer, and may satisfy 0.8≤x≤1.2, preferably 1.00≤x≤1.02.

[0062] y represents the molar ratio of Co in the coating layer, and may satisfy 0.5≤y≤1.5, preferably 0.8≤y≤1.2.

[0063] The coating layer may block contact between the cathode active material and the electrolyte contained in the lithium secondary battery to suppress the occurrence of a side reaction, thus improving lifespan properties, and further, may increase the packing density of the cathode active material.

[0064] The coating layer may be formed on the entire surface of the positive electrode active material, or may be partially formed. Specifically, when the coating layer is partially formed on the surface of the positive electrode active material, the coating layer may be formed to be 20% or more of the total area of ​​the positive electrode active material. When the area of ​​the coating layer is less than 20%, the effects of improving the life properties and improving the packing density brought about by the formation of the coating layer may not be significant.

[0065] In addition, the coating layer may be formed at a thickness ratio of 1 / 10000 to 1 / 100 relative to the average particle size of the positive electrode active material particles. If the thickness ratio of the coating layer relative to the positive electrode active material particles is less than 1 / 10000, the effects of improving the life properties and improving the packing density brought about by the formation of the coating layer are not significant, and if the thickness ratio is greater than 1 / 100, there is a risk that the battery properties may deteriorate.

[0066] Method for preparing positive electrode active material

[0067] The preparation method of the positive electrode active material of the present invention may include: preparing a nickel-based lithium composite metal oxide in which the Ni content in transition metals other than lithium is 80 atomic % or more, mixing the nickel-based lithium composite metal oxide with a solution containing a cobalt raw material, and then performing a first heat treatment to form a coating layer on the surface of the nickel-based lithium composite metal oxide.

[0068] First, a nickel-based lithium composite metal oxide in the form of single particles, quasi-single particles, or a combination thereof, in which the nickel content of metal elements other than lithium is 80 atomic % or more, can be prepared.

[0069] The nickel-based lithium composite metal oxide can be a commercially available product for purchase and use, or it can be prepared using a manufacturing method of nickel-based lithium composite metal oxides known in the art. For example, the nickel-based lithium composite metal oxide can be prepared by mixing a lithium raw material with a nickel-based lithium composite metal oxide precursor and then firing the mixture.

[0070] The nickel-based lithium composite metal oxide precursor can be represented, for example, by the following [Formula A] or [Formula B].

[0071] [Formula A]

[0072] [Ni p Co q M 1 r M 2 s (OH)2

[0073] [Formula B]

[0074] [Ni p Co q M 1 r M 2 s O·OH

[0075] In the above Formula A and Formula B, M 1 can be one or more selected from Mn and Al, and preferably, it can be Mn or a combination of Mn and Al.

[0076] In the above Formula A and Formula B, M 2 can be one or more selected from the group consisting of Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, F, P, S, and Y.

[0077] p represents the molar ratio of nickel among the metal elements in the precursor, and it can satisfy 0.80 ≤ p < 1.0, 0.80 ≤ p ≤ 0.98, or 0.80 ≤ p ≤ 0.95.

[0078] q represents the molar ratio of cobalt among the metal elements in the precursor, and it can satisfy 0 < q ≤ 0.2, 0 < q ≤ 0.15, or 0.01 ≤ q ≤ 0.10.

[0079] r represents the molar ratio of the M 1 element among the metal elements in the precursor, and it can satisfy 0 < r ≤ 0.2, 0 < r ≤ 0.15, or 0.01 ≤ r ≤ 0.1.

[0080] s represents the molar ratio of the M 2 element among the metal elements in the precursor, and it can satisfy 0 ≤ s < 0.1 or 0 ≤ s ≤ 0.05.

[0081] The lithium raw material can be, for example, at least one selected from the group consisting of lithium carbonate (Li2CO3), lithium hydroxide (LiOHH2O), anhydrous lithium hydroxide (LiOH), LiNO3, CH3COOLi and Li2(COO)2, preferably, it can be lithium carbonate (Li2CO3), lithium hydroxide (LiOHH2O) or a combination thereof.

[0082] When preparing the positive electrode active material, the nickel-based lithium composite metal oxide precursor and the lithium raw material can be mixed so that the molar ratio of Li: transition metal is 1:1 to 1.3:1, preferably 1:1 to 1.1:1. When the mixing ratio of the nickel-based lithium composite metal oxide precursor and the lithium raw material meets the above range, the crystal structure of the positive electrode active material can be smoothly developed, and a positive electrode active material with excellent physical properties can be prepared. When the content of the lithium raw material is too small, the crystal structure will not develop normally, and when the content is too large, unreacted Li will remain as a by-product, which may lead to capacity degradation, gas production, etc.

[0083] When conditions such as the firing temperature and time are appropriately adjusted, the average particle size of the nodules of the nickel-based lithium composite metal oxide can be adjusted to an appropriate range.

[0084] The firing may be performed at a temperature of 700°C to 1000°C, preferably 700°C to 900°C, and more preferably 700°C to 850°C. When the firing temperature is lower than 700°C, the raw materials may remain in the particles due to insufficient reaction, thereby deteriorating the high temperature stability of the battery, and the volume density and crystallinity may deteriorate, thereby reducing the structural stability. At the same time, when the firing temperature exceeds 1000°C, the particles may grow unevenly, and the disintegration of the particles may become difficult, resulting in capacity degradation, etc.

[0085] The firing may be performed for 5 to 24 hours, preferably 10 to 24 hours. When the firing time is less than 5 hours, the reaction time is too short to obtain a highly crystalline positive electrode active material, and when it is greater than 24 hours, the particle size may become too large and the production efficiency may deteriorate.

[0086] Next, the prepared nickel-based lithium composite metal oxide and a solution containing a cobalt raw material may be mixed and heat-treated to form a coating layer on the surface of the nickel-based lithium composite metal oxide.

[0087] Specifically, the nickel-based lithium composite metal oxide and a solution containing a cobalt raw material may be mixed, stirred, filtered and separated, and then heat-treated in an oxygen atmosphere.

[0088] Based on 100 parts by weight of the nickel-based lithium composite metal oxide, the mixing amount of the cobalt raw material can be 0.8 to 5 parts by weight, preferably 1 to 4 parts by weight, and more preferably 1.5 to 3 parts by weight. When the content of the cobalt raw material satisfies the above range, the occurrence of cracking at the interface between nodules is suppressed, thereby improving stability and initial capacity.

[0089] As the cobalt raw material, for example, cobalt acetate, cobalt sulfate, cobalt chloride, cobalt nitrate, or the like can be used.

[0090] Meanwhile, the solution containing the cobalt raw material may be prepared by dissolving the cobalt raw material in a solvent such as water or ethanol.

[0091] When the nickel-based lithium composite metal oxide is added to a solution containing a cobalt raw material, mixed, and then stirred, the cobalt contained in the solution reacts with lithium byproducts present on the surface of the nickel-based lithium composite metal oxide to form a coating layer on the surface.

[0092] Then, by performing filtration separation and then performing heat treatment, a nickel-based lithium composite metal oxide powder having a coating layer formed thereon was obtained.

[0093] At this time, filtration can be performed by placing filter paper in a filtration bottle and then performing vacuum decompression, and drying can be performed at 100 to 180° C., preferably 120 to 160° C., for 10 to 24 hours, preferably 12 to 22 hours.

[0094] The heat treatment is intended to form a coating layer by fixing cobalt on the surface of the nickel-based lithium composite metal oxide, and can be performed at a temperature of 630° C. to 800° C., preferably 650° C. to 750° C. When the heat treatment temperature is within the above range, the cobalt raw material reacts sufficiently with the lithium byproduct on the surface, so that the coating layer is easily formed.

[0095] The heat treatment may be performed for 3 to 8 hours, preferably 4 to 7 hours. When the heat treatment time is within the above range, a coating layer of an appropriate thickness may be formed, and production efficiency may be improved.

[0096] positive electrode

[0097] The positive electrode of the present invention comprises the positive electrode active material of the present invention described above. Specifically, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material of the present invention. Since the positive electrode active material has been described above, a detailed description thereof will be omitted, and hereinafter, only the remaining components will be described in detail.

[0098] The positive electrode current collector of the present invention may include a metal with high conductivity, and there is no particular limitation, as long as the positive electrode active material layer is easily adhered thereto and the positive electrode current collector is not reactive within the voltage range of the battery. As the positive electrode current collector, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. may be used. In addition, the thickness of the positive electrode current collector may generally be 3 μm to 500 μm, and fine concavo-convex objects may be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, a sheet, a foil, a mesh, a porous body, a foam, a non-woven fabric body, and the like.

[0099] Based on the weight of all positive active materials contained in the positive active material layer, the content of the positive active material contained in the positive active material layer of the present invention can be 95% by weight to 100% by weight, preferably 98% by weight to 100% by weight, and more preferably 99% by weight to 100% by weight. Most preferably, only 100% of the positive active material in the form of a single particle or a quasi-single particle can be included. When the content of the positive active material of the present invention satisfies the above range, sufficient life performance can be obtained. This is because, when the content of the positive active material in the form of secondary particles is greater than 5% by weight of all positive active materials, fine powder is generated by the secondary particles during electrode manufacturing and charge and discharge processes, and the side reaction with the electrolyte increases, thereby reducing the effect of suppressing gas production.

[0100] The positive electrode active material layer of the present invention may optionally contain a conductive material and a binder together with the positive electrode active material, if necessary.

[0101] At this time, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt %, based on the total weight of the positive electrode active material layer. When the positive electrode active material is included within the above content range, excellent capacity properties can be exhibited.

[0102] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation, as long as it has electronic conductivity and does not cause chemical changes in the constructed battery. Some examples of conductive materials may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal carbon black, and carbon fiber; metal powders or metal fibers, such as copper, nickel, aluminum, and silver; conductive tubes, such as carbon nanotubes; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used. The content of the conductive material may be 0.1 wt % to 15 wt % based on the total weight of the positive electrode active material layer.

[0103] Binders are used to improve the bonding between the positive active material particles and the adhesion between the positive active material and the current collector. Some examples of binders may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, polymers in which hydrogen is replaced by Li, Na or Ca, or various copolymers thereof, and any one or a mixture of two or more thereof may be used. Based on the total weight of the positive active material layer, the content of the binder may be 0.1 wt % to 15 wt %.

[0104] The positive electrode can be manufactured by a conventional positive electrode manufacturing method. Specifically, a positive electrode active material is prepared, and a positive electrode active material layer forming composition prepared by optionally dissolving or dispersing a binder, a conductive material, and a dispersant in a solvent as necessary can be prepared. The positive electrode active material layer forming composition can be applied, dried, and then rolled to manufacture the positive electrode.

[0105] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc., and any one thereof or a mixture of two or more thereof may be used. If the coating thickness and productivity of the slurry are taken into consideration, the solvent may dissolve or disperse the positive electrode active material, the conductive material, the binder, and the dispersant, and thereafter make the slurry have a viscosity capable of showing excellent thickness uniformity when used to manufacture the positive electrode, then the amount of the solvent is sufficient.

[0106] In addition, in another method, the positive electrode may be manufactured by casting the positive electrode active material layer-forming composition on a separate support and then laminating the film peeled off from the support on the positive electrode current collector.

[0107] Electrochemical Devices

[0108] Next, the electrochemical device of the present invention will be described. The electrochemical device of the present invention includes the positive electrode of the present invention described above, and the electrochemical device may be specifically a battery, a capacitor, etc., and more specifically, may be a lithium secondary battery.

[0109] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode arranged opposite to the positive electrode, a separator and an electrolyte inserted between the positive electrode and the negative electrode. Since the positive electrode is the same as above, its detailed description will be omitted, and hereinafter, only the remaining components will be described in detail.

[0110] In addition, the lithium secondary battery may optionally further include a battery case for accommodating an electrode assembly of a positive electrode, a negative electrode, and a separator, and a sealing member for sealing the battery case.

[0111] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0112] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and as in the case of the positive electrode current collector, fine concavoconvex objects can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven fabric body.

[0113] The negative electrode active material layer may optionally contain a binder and a conductive material in addition to the negative electrode active material.

[0114] As the negative electrode active material, a compound that can reversibly intercalate and deintercalate lithium can be used. Some examples of the negative electrode active material may include: carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite comprising a metal compound and a carbon material, such as a Si-C composite or a Sn-C composite, and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon, etc. can be used as carbon materials. Representative examples of low-crystalline carbon may include soft carbon and hard carbon, and representative examples of high-crystalline carbon may include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbons such as petroleum or coal tar pitch-derived coke.

[0115] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0116] The binder is a component used to assist the bonding between the conductive material, the active material and the current collector, and is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, various copolymers thereof, and the like.

[0117] The conductive material is a component for further improving the conductivity of the negative electrode active material, and its addition amount may be 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal carbon black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. may be used.

[0118] The negative electrode active material layer can be prepared by applying a negative electrode active material layer forming composition prepared by dissolving or dispersing the negative electrode active material and optional binder and conductive material in a solvent on the negative electrode collector and then drying; or it can be prepared by casting the negative electrode active material forming composition on a separate carrier and then stacking the film layer peeled off from the carrier on the negative electrode collector.

[0119] Meanwhile, in lithium secondary batteries, the diaphragm is used to separate the negative electrode from the positive electrode, and to provide a mobile path for lithium ions, and any diaphragm can be used without particular limitation, as long as it is a diaphragm commonly used in lithium secondary batteries, in particular, preferably a diaphragm with low resistance to ion movement in the electrolyte and excellent electrolyte moisture retention capacity. Specifically, as a diaphragm, a porous polymer film can be used, for example, a porous polymer film made using a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc.), or a laminated structure with more than two layers thereof. In addition, conventional porous nonwoven fabrics can be used, for example, nonwoven fabrics made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used with a single layer or multilayer structure.

[0120] In addition, the electrolyte used in the present invention can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used when manufacturing a lithium secondary battery, but the electrolyte is not limited thereto.

[0121] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0122] As an organic solvent, any organic solvent can be used without particular limitation, as long as it can act as a medium through which the ions involved in the electrochemical reaction of the battery can move. Specifically, as an organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol or isopropanol; nitriles such as R-CN (wherein R is a straight chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; cyclopentane sulfone, etc. Among them, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity straight-chain carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) which can improve the charge and discharge performance of the battery.

[0123] Any compound may be used as the lithium salt without particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt may be selected from F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2- 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - At least one of the group consisting of, and as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2) 2。 LiCl, LiI, LiB(C2O4)2, etc. The lithium salt can be used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thereby exhibiting excellent performance, and lithium ions can be efficiently moved.

[0124] In the electrolyte, in order to improve the life properties of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, more than one additive may be included, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride, etc. At this time, based on the total weight of the electrolyte, the content of the additive may be 0.1 wt % to 5 wt %.

[0125] As described above, the lithium secondary battery comprising the positive electrode of the present invention stably exhibits excellent discharge capacity, output properties and life properties, and therefore, can be used in the field of portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0126] Therefore, according to another embodiment of the present invention, a battery module including a lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0127] The battery module or battery pack may be used as a power source for one or more medium-to-large devices in power tools, electric vehicles including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs), or power storage systems.

[0128] The outer shape of the lithium secondary battery of the present invention is not particularly limited, but may be cylindrical using a can, square, pouch, coin, or the like.

[0129] The lithium secondary battery of the present invention can be used in a battery cell used as a power source for small devices, and can also be preferably used as a unit cell in a medium or large battery module including a plurality of battery cells.

[0130] Examples of medium and large-scale equipment include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0131] Example

[0132] Example 1

[0133] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide was in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules was 5.69 μm.

[0134] 0.67 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 6.25μm and the XY / Z value is 1.82.

[0135] The positive electrode active material, carbon nanotubes and PVdF as a binder were mixed in an NMP solvent at a weight ratio of 97.5:1.0:1.5 to prepare a positive electrode slurry. The positive electrode slurry was coated on one surface of an aluminum current collector (thickness of 12 μm), dried at 130°C to form a positive electrode active material layer on the aluminum current collector, and then rolled to manufacture a positive electrode.

[0136] Meanwhile, graphite as negative electrode active materials, carbon-based conductive material (SuperC65), carboxymethyl cellulose (Daicell 2200) and styrene-butadiene rubber binder (BM-L302) were mixed in a weight ratio of 96:20.5:21:2.5 and added to water as a solvent to prepare negative electrode slurry. The negative electrode forming composition was coated on a copper foil having a thickness of 8 μm, dried and then rolled to manufacture a negative electrode.

[0137] The positive electrode and negative electrode prepared above were stacked together with a polyolefin separator to manufacture an electrode assembly, and then the electrode assembly was placed in a battery case, and an electrolyte was injected into the battery case, in which 1M LiPF6 was dissolved in a mixed solvent prepared by mixing ethylene carbonate:diethyl carbonate in a ratio of 3:7.

[0138] Example 2

[0139] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide is in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules is 5.56 μm.

[0140] 1 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 5.96μm and the XY / Z value is 2.80.

[0141] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0142] Example 3

[0143] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide is in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules is 4.18 μm.

[0144] 0.5 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 5.86μm and the XY / Z value is 1.07.

[0145] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0146] Comparative Example 1

[0147] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH so that the molar ratio of Li / Me(Ni, Co, Mn) was 1.05, and heat treated at 920°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide was in the form of quasi-single particles composed of a number of nodules, and the average particle size (μm) of the nodules was 2.15 μm.

[0148] 0.67 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 7.93μm and the XY / Z value is 0.54.

[0149] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0150] Comparative Example 2

[0151] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH so that the molar ratio of Li / Me(Ni, Co, Mn) was 1.05, and heat treated at 920°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide was in the form of quasi-single particles composed of a plurality of nodules, and the average particle size (μm) of the nodules was 1.1 μm.

[0152] 1 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 6.38μm and the XY / Z value is 0.52.

[0153] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0154] Comparative Example 3

[0155] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH so that the molar ratio of Li / Me(Ni, Co, Mn) was 1.05, and heat treated at 920°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide was in the form of quasi-single particles composed of a plurality of nodules, and the average particle size (μm) of the nodules was 1.1 μm.

[0156] 2 moles of the cobalt raw material Co3O4 were added to 100 moles of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 3.15μm and the XY / Z value is 4.305.

[0157] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0158] Comparative Example 4

[0159] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide was in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules was 3.05 μm.

[0160] 0.67 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 3.50μm and the XY / Z value is 1.726.

[0161] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0162] Comparative Example 5

[0163] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide is in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules is 1.69 μm.

[0164] 1 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 5.76μm and the XY / Z value is 0.88.

[0165] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0166] Comparative Example 6

[0167] Ni as a precursor 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed with LiOH to make the molar ratio of Li / Me(Ni, Co, Mn) be 1.05, and heat treated at 900°C in an oxygen atmosphere for 10 hours to prepare a lithium composite transition metal oxide LiNi 0.8 Co 0.1 Mn 0.1 The prepared nickel-based lithium composite metal oxide is in the form of quasi-single particles consisting of 1 to 3 nodules, and the average particle size (μm) of the nodules is 2.26 μm.

[0168] 1.5 mol of the cobalt raw material Co3O4 was added to 100 mol of the prepared nickel-based lithium composite metal oxide, and the mixture was calcined at 700°C for 5 hours. 50 It is 3.15μm and the XY / Z value is 3.22.

[0169] A positive electrode and a lithium secondary battery including the positive electrode were manufactured in the same manner as in Example 1, except that the positive electrode was manufactured using the above-mentioned positive electrode active material.

[0170] Experimental Example 1 - Evaluation of Lifespan Properties

[0171] Each lithium secondary battery prepared in Examples 1 to 3 and Comparative Examples 1 to 6 was charged to 4.25 V at a constant current of 0.5 C at 45° C., and discharged to 2.5 V at a constant current of 0.5 C, wherein the charge and discharge was set as one cycle, and the capacity retention rate after 50 cycles was measured, which is shown in Table 1 below.

[0172] [Table 1]

[0173] Capacity retention after 50 cycles (%) Example 1 92.9 Example 2 91.1 Example 3 90.8 Comparative Example 1 86.9 Comparative Example 2 85.0 Comparative Example 3 88.3 Comparative Example 4 88.2 Comparative Example 5 86.4 Comparative Example 6 86.7

[0174] As shown in Table 1 above, it has been confirmed that by including the conditions satisfying [Formula 1] 1≤XY / Z≤3 and D 50 The lithium secondary batteries of Examples 1 to 3 manufactured by using a positive electrode active material having a D of 5 μm to 12 μm are different from those manufactured by using a positive electrode active material having a D of 5 μm to 12 μm. 50 Compared with the lithium secondary batteries of Comparative Examples 1 to 6 manufactured using positive electrode active materials having a diameter (μm) not satisfying 5 μm to 12 μm, the lithium secondary batteries have excellent life properties.

[0175] Experimental Example 2 - High Temperature Storage Properties

[0176] Each positive electrode active material prepared in Examples 1 to 3 and Comparative Examples 1 to 6, a carbon black conductive material, and a PVdF binder were mixed in an N-methylpyrrolidone solvent at a weight ratio of 96:2:2 to prepare a positive electrode mixture material (viscosity: 5000 mPa·s), and the mixture material was coated on one surface of an aluminum current collector, dried at 130° C., and then rolled to manufacture a positive electrode. Lithium metal was used as a negative electrode.

[0177] A porous polyethylene separator is inserted between the positive and negative electrodes manufactured as described above to manufacture an electrode assembly, the electrode assembly is placed in a shell, and an electrolyte is injected into the shell to manufacture a lithium secondary battery. At this time, the electrolyte is prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0M in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (mixed volume ratio EC / EMC / DEC=3 / 4 / 3). Each lithium secondary battery half-cell manufactured as described above is charged at 0.2C in CCCV mode until 4.25V (end current 1 / 20C). After charging, two charged positive electrodes and two polyethylene separators obtained by disassembling the cell are alternately stacked on the bottom plate of the coin cell, the electrolyte is injected therein, and then the coin cell is assembled again. Thereafter, gas chromatography-mass spectrometry (GC-MS) is used to measure the gas generated by storing the coin cell for 2 weeks at 70°C. The results are shown in Table 2 below.

[0178] [Table 2]

[0179] Gas production in 2 weeks Example 1 29 Example 2 37 Example 3 42 Comparative Example 1 79 Comparative Example 2 68 Comparative Example 3 75 Comparative Example 4 62 Comparative Example 5 67 Comparative Example 6 69

[0180] As shown in Table 2 above, it has been confirmed that by including the conditions satisfying [Formula 1] 1≤XY / Z≤3 and D 50 The lithium secondary batteries of Examples 1 to 3 manufactured by using a positive electrode active material having a D of 5 μm to 12 μm and a positive electrode active material having a D of 5 μm to 12 μm are different from those manufactured by using a positive electrode active material having a D of 5 μm to 12 μm and a positive electrode active material having a D of 5 μm to 12 μm. 50 Compared with the lithium secondary batteries of Comparative Examples 1 to 6 manufactured using positive electrode active materials having a diameter (μm) not satisfying 5 μm to 12 μm, the lithium secondary batteries have excellent high temperature storage properties.

Claims

1. A positive electrode active material comprising: A nickel-based lithium composite metal oxide containing 80 atomic % or more of Ni in a transition metal other than lithium, wherein: The nickel-based lithium composite metal oxide is in the form of a single particle or a quasi-single particle; and a coating layer on the surface of the nickel-based lithium composite metal oxide, wherein the coating layer contains cobalt, Wherein, the positive electrode active material satisfies the following formula 1: [Formula 1] 1≤XY / Z≤3 Wherein, in the above formula 1, X in mol% is the molar number of Co in the coating layer based on 100 mol of the nickel-based lithium composite metal oxide, Y in μm is the average particle size of the nodules of the nickel-based lithium composite metal oxide, and Z in μm is the D of the positive electrode active material. 50 , and Z is 5 μm to 12 μm.

2. The positive electrode active material according to claim 1, wherein The nickel-based lithium composite metal oxide is represented by the following formula 2: [Formula 2] Li a Ni b Co c M 1 d M 2 e O2 Wherein, in the above formula 2, M 1 is Mn, Al or a combination thereof, M 2 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, and 0.8≤a≤1.2, 0.8≤b<1, 0 <c<0.2,0<d<0.2,0≤e≤0.1。 3. The positive electrode active material according to claim 1, wherein X is 1 mol % to 5 mol %.

4. The positive electrode active material according to claim 1, wherein Y is 1 μm to 10 μm.

5. The positive electrode active material according to claim 1, wherein The ratio of Z to Y, Z / Y, is 1 to 3.

6. The positive electrode active material according to claim 1, wherein The positive electrode active material includes 1 mol % to 5 mol % of lithium by-products relative to the nickel-based lithium composite metal oxide.

7. The positive electrode active material according to claim 1, wherein The average grain size of the nickel-based lithium composite metal oxide is 170 nm to 300 nm.

8. The positive electrode active material according to claim 1, wherein The strain value of the nickel-based lithium composite metal oxide is 200×10 -6 Up to 380×10 -6 . 9 . A positive electrode comprising a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to claim 1 .

10. The positive electrode according to claim 9, wherein The positive electrode active material may be included in an amount of 90 wt % to 100 wt % relative to the total weight of the positive electrode active material included in the positive electrode.

11. The positive electrode according to claim 9, wherein The ratio of the positive electrode active material having a size of 5 μm to 7 μm is 80 volume % or more relative to the entire positive electrode active material. 12 . A lithium secondary battery comprising: the positive electrode according to claim 9 ; a negative electrode; and an electrolyte.